A Higher Ovarian Response after Stimulation for IVF Is Related to a Higher Number of Euploid Embryos. (27th March 2017) - Labarta, Elena; Bosch, Ernesto; Mercader, Amparo; Alamá, Pilar; Mateu, Emilia; Pellicer, Antonio
Abstract : This study has analysed the relationship between ovarian response and the number of euploid embryos. This is a post hoc analysis of a subset of data generated during a prospective cohort study previously published. Forty-six oocyte donors were subjected to ovarian stimulation with 150 IU of rFSH and 75 IU of hp-hMG in a GnRH agonist long protocol. Preimplantation genetic screening was performed in all viable embryos. We observed a positive relationship between ovarian response and the number of euploid embryos. When ovarian response was above the median (≥17 oocytes), the mean number of euploid embryos per donor was 5.0 ± 2.4, while when <17 oocytes were obtained the mean number of euploid embryos was 2.7 ± 1.4 (p = 0.000 ). Aneuploidy rate did not increase with ovarian response or gonadotropin doses. Also, the number of euploid embryos was inversely related to the amount of gonadotropins needed per oocyte obtained (ovarian sensitivity index). These results suggest that the number of euploid embryos available for embryo transfer increases as the number of oocytes obtained does. Considering the total number of euploid embryos seems more relevant than the aneuploidy rate.